Quantitative and qualitative benefits of translanguaging pedagogic practice among first graders in multilingual classrooms of Lundazi district in Zambia (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
The aim of the paper is assess the pedagogical benefits of translanguaging using a quasi-experiment where two literacy classes with similar sociolinguistic composition were taught differently. In this case, the control class strictly followed the ‘monolingual’ language policy while the experimental class was taught using translanguaging. The idea was to see whether translanguaging could lead to any measurable literacy development benefits on the learner. Through interviews with the class teacher and classroom observations, the paper also sought to bring out the qualitative benefits which were observed or experienced throughout the experiment. A total of 82 pupils participated in the study with one teacher who taught both classes. Quantitative data was analysed using SPSS and a Levene’s test of variance was used to analyse the test results while thematic analysis was used for qualitative data analysis. Post experimental test results showed higher average mean scores for the experimental group (M=15.10) than the control group (M=11.71). The Cohen’s d=0.98 for the post-test showed the large effect size above .8. The performance of learners in the experimental group was significantly different from the control group [t (52.960 = 4.454, p